Energy yields from anaerobic digestion of palm oil mill effluent - Ng, W. J.; Chin, K. K.; Wong, K. K. (Elsevier Ltd., 1987)
Three different suspended-growth anaerobic digestion configurations-the mesophilic one-stage, the mesophilic two-phase and the thermophilic one-stage, were used to treat palm oil mill effluent (POME) and their performances compared. The mesophilic two-phase process showed the highest energy yields which reached 20 542 J g-1 COD utilized at a hydraulic retention time of 31 days. However, high energy yields did not coincide with high TCOD removals. The latter was a characteristic of the thermophilic process. The relatively poor TCOD removal in the two-phase system was due to its lower efficiency in VSS removal. At hydraulic retention times of 25 days and more the mesophilic one-stage process had higher energy yields than the thermophilic process. Anaerobic digestion was found to be an effective means for POME treatment. © 1987.